People's Republic of China : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2011)
This report discusses the IMF/World Bank Financial Sector Assessment Program (FSAP) exercise for China undertaken during June-December 2010. The assessment concluded that reforms in China have progressed well in moving toward a more commercially oriented financial system. Despite success and rapid growth, China's financial sector is confronting several near-term risks, structural challenges, and policy-induced distortions. A properly composed and timely implemented set of reforms would help address these challenges. A framework to resolve weak financial institutions on a timely basis is also needed.